CFD modeling of turbulent convection heat transfer of nanofluids containing green functionalized graphene nanoplatelets flowing in a horizontal tube: Comparison with experimental data - Sadri, Rad; Mallah, Abdul Rahman; Hosseini, Maryam; Ahmadi, Goodarz; Kazi, Salim Newaz; Dabbagh, Ali; Yeong, Chai Hong; Ahmad, Roslina; Yaakup, Nur Adura (Elsevier, 2018)
In this research, a series of numerical simulations were conducted utilizing computational fluid dynamics (CFD) software in order to predict the heat transfer performance of queues nanofluids containing clove-treated graphene nanoplatelets (CGNPs) flowing in a horizontal stainless steel heated pipe. The GNPs were covalently functionalized with clove buds using free radical grafting reaction using an eco-friendly process. The advantage of this synthesis method was that it did not use hazardous acids, which are typically used in traditional treatment methods of carbon nanostructures. The thermo-physical properties of the aqueous nanofluids obtained experimentally were used as inputs for the CFD simulations for solving the governing equations of heat transfer and fluid motion. The shear stress transport (SST) k-ω turbulence model was also used in these simulations. The corresponding convective heat transfer coefficient and friction factor of aqueous nanofluids for nanoparticle weight concentrations of 0.025, 0.075, and 0.1% were evaluated. The simulation results for both heat transfer coefficient and friction factor were shown to be in agreement with the experimental data with an average relative deviation of about ±10%. The presented results confirmed the applicability of the numerical model for simulating the heat transfer performance of CGNPs aqueous nanofluids in turbulent flow regimes.